RELIGIOUS EXPRESSIONS AND THEIR PRAGMATIC FUNCTIONS IN ENGLISH RELIGIOUS DISCOURSE - Khudoynazarova Uglonoy Allamurodovna (Modern American Journals, 2025)
This study investigates religious discourse in English and Uzbek contexts, concentrating on fixed expressions, pragmatic functions, and metaphorical meanings. It analyzes the influence of cultural, theological, and linguistic factors on discourse formation, emphasizing the importance of speech acts, implicit meaning, and intertextual connections. Particular focus is placed on expressions relating to God, Christ, and sacred writings, illustrating both universal patterns and culturally distinct features of religious language.
Keywords: Theolinguistics, stable expressions, religion, religious language, pragmatic functions, implicit meaning.